P89 Emicizumab development in paediatric patients with congenital hemophilia A and inhibitors against factor VIII. Issue 6 (17th May 2019) - Schmitt, C; Yoneyama, K; Chang, T; Retout, S; Grimm, H -P; Levy, GG
Abstract : Background: Emicizumab, a bispecific monoclonal antibody, bridges activated factor (F) IX (FIXa) and FX, restoring missing FVIIIa function in patients with hemophilia A (PwHA). It has been recently approved for routine prophylaxis of bleeding episodes in PwHA with FVIII inhibitors in all age groups. We herein describe the paediatric development of emicizumab with a focus on dose selection, study design and extrapolation of efficacy. Methods: The dosing regimen for the HAVEN 1 study (adolescents/adults) was selected based on the exposure-response (annualized bleeding rate [ABR]) relationship derived from a phase I/II study in adolescent/adult PwHA. Pharmacokinetic (PK) simulations, with or without maturation of clearance (CL MAT), were performed to guide selection of the dosing regimen for the HAVEN 2 study (paediatrics) aiming to achieve the same target exposure as in HAVEN 1. HAVEN 2 employed a flexible design with possibility for individual- and population-level dose up-titration. Additional PK modeling and simulations together with exposure-response analyses were used to support full extrapolation of efficacy in any age category where no data was available. Results: 1.5 mg/kg/week in HAVEN 1 provided mean trough concentrations of ∼50 µg/mL and was associated with a 87% reduction in ABR. Doses of ≥ 1.5 (with CL MAT) and ≥ 2.25 mg/kg/week (without CL MAT) were predicted to achieve this target exposure in children. HAVEN 2 began by investigating the same dose as HAVEN 1. Similar trough concentrations of ∼ 50 µg/mL were achieved in children and were associated with low ABR. No patients < 1 year were enrolled in HAVEN 2. PK simulations and pharmacological rationale suggested that a different dose for these patients was not warranted. Conclusions: Efficacy of emicizumab in adolescents/adults was demonstrated in HAVEN 1, partially extrapolated to HAVEN 2 participants 1–11 year of age, and fully extrapolated in patients < 1 year. Disclosure(s): Authors are Roche/Genentech employees